Double standards in spring trap welfare: ending inequality for rats (Rodentia: Muridae), mice (Rodentia: Muridae) and moles (Insectivora: Talpidae) in the United Kingdom - Baker, S; Macdonald, D; Ellwood, S (International Conference on Urban Pests, 2017)
Spring traps require welfare approval in the UK, but break-back traps, for rats and mice, and mole traps are exempt. Mechanical tests on a wide range of these unregulated traps showed that impact momentum varied 6-8-fold, and clamping force varied 4-5.5-fold, among traps for use with each of rats, mice and moles. There was considerable overlap between the strongest mouse traps and weakest rat traps for each force. A post-mortem and x-ray study of 50 spring-trapped moles revealed that none sustained damaged skulls or cervical vertebrae; they were, therefore, unlikely to have become unconscious immediately. Some moles appeared superficially to have broken spines, but in fact they had incurred only soft tissue damage and no broken vertebrae. The primary identifiable cause of death in trapped moles was acute haemorrhage. A minority of moles may have asphyxiated, but evidence for this was weak. Given the scale of rat, mouse and mole trapping in the UK, the wide range of unregulated traps available, and doubts raised regarding their humaneness, this research suggests an urgent imperative to abandon a puzzling double standard, and thereby to reduce the welfare impact of unregulated spring traps for rats, mice and moles. There is a strong case that all traps should be subjected to comparable approval standards. In the meantime, we propose a Voluntary Trap Approval (VTA) scheme under which manufacturers would submit traps for approval testing in the same way as for regulated traps. All approved traps could be given a certification mark and trap suppliers might choose to sell only approved traps, thus edging non-approved traps out of the market.